Forming‐free resistive switching characteristics and improved reliability in sub‐stoichiometric NbNx films. Issue 4 (6th March 2015) - Kim, Hee‐Dong; Yun, Min Ju; Kim, Tae Geun
Abstract : In this study, we demonstrate forming‐free and reliable resistive switching (RS) characteristics by controlling the stoichiometry of niobium nitride (NbN x ) films. Compared to a perfect stoichiometric NbN x film, a decrease of 6% nitrogen content and an increase of 5% O2 content are found in the sub‐stoichiometric NbN x sample (s‐NbN x ), and a structural change for the s‐NbN x film is observed from X‐ray diffraction results, which results in the possibility of abundant defect generation in the s‐NbN x film at virgin state. In the RS test, the s‐NbN x film normally carries out well without initial forming because of the already‐formed conducting filaments; in particular, in the reliability study, the s‐NbN x film shows more stable dc cycling characteristics for 1000 cycles without any degradation and smaller variations in the operating current and voltage characteristics. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The authors demonstrate forming‐free resistive switching (RS) characteristics for the sub‐stoichiometry of niobium nitride (s‐NbN x ) films because of its leaky characteristics at virgin state. Particularly, in the reliability study, the s‐NbN x film shows stable dc cycling characteristics for 1000 cycles and small variations in the operating current and voltage characteristics.